2022
DOI: 10.3390/ijms232314672
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Response in Cancer Therapy and Resistance: Challenges and Opportunities

Abstract: Resistance to chemo- and radiotherapy is a common event among cancer patients and a reason why new cancer therapies and therapeutic strategies need to be in continuous investigation and development. DNA damage response (DDR) comprises several pathways that eliminate DNA damage to maintain genomic stability and integrity, but different types of cancers are associated with DDR machinery defects. Many improvements have been made in recent years, providing several drugs and therapeutic strategies for cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 301 publications
0
37
0
Order By: Relevance
“…[234][235][236] Research findings have linked the prochelator's antineoplastic efficiency to cellular GGT activity. 237 A 24-hour survey reports a half maximum inhibitory doses in the range of 800 nM in prostate cancer cell lines 22Rv1 and LNCaP to over 15 µM in normal prostate PWR-1E cells. These findings suggest a novel method for leveraging prostate cancer's…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…[234][235][236] Research findings have linked the prochelator's antineoplastic efficiency to cellular GGT activity. 237 A 24-hour survey reports a half maximum inhibitory doses in the range of 800 nM in prostate cancer cell lines 22Rv1 and LNCaP to over 15 µM in normal prostate PWR-1E cells. These findings suggest a novel method for leveraging prostate cancer's…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…The targeting of DDR has become increasingly relevant in recent years due to the discovery of deleterious mutations in genes involved in various DDR pathways, which often results in loss of function of the corresponding DNA repair proteins. In particular, the inhibition of PARP1/2 activity has become a cornerstone of treatment for advanced cancers with DDR de ciencies and has been extensively studied in the literature [70]. However, it has also been reported that increase in the gene expression level of DDR genes may lead to resistance to cisplatin chemotherapy [71], while the overexpression of BRCA1, BRCA2, RAD51, and RPA1 has been observed in hypopharyngeal and nasopharyngeal carcinoma cells resistant to radiotherapy [72].…”
Section: Discussionmentioning
confidence: 99%
“…Cai and his colleagues found that PDPK1i+MEKi is an effective immunostimulatory approach counter to NRAS mutant melanoma. Genetic instability in several types of cancer contributes to acquiring a phenotype needed for colonising distant organs, and metastatic progression correlates with an increase in mutation burden and alteration of genes involved in DNA damage response [ 57 ]. We need to understand better the mechanisms that hinder a cell from tolerating genomic instability and the cellular consequences of exceeding a genomic instability limit…”
Section: Discussionmentioning
confidence: 99%